Upaya Mitigasi Risiko Pasar Pembiayaan Cicil Emas Bank Syariah Indonesia Kantor Cabang Adam Malik Kota Bengkulu - Ani Khusnul Hatimah; Supardi Mursalin; Katra Pramadeka (Universitas Muhammadiyah Surabaya, 2026)
This study aims to identify the forms of market risk and analyze market risk mitigation efforts in gold installment financing at Bank Syariah Indonesia's Adam Malik Branch Office in Bengkulu City. This study employed a qualitative method with a descriptive approach. Data sources consisted of primary and secondary data. Primary data were obtained through in-depth interviews and observations of pawning officers and customers using gold installment products, while secondary data were obtained from official bank documents, standard operating procedures (SOPs), and relevant literature. Data collection techniques included interviews, observation, and documentation. Data analysis utilized the stages of data reduction, data presentation, and conclusion drawing, referring to the ISO 31000:2018 risk management framework. The results indicate that the primary market risk stems from gold price fluctuations, which impact the value of collateral and potentially lead to losses for the bank. Risk mitigation efforts include customer eligibility analysis, setting appropriate margins, regular gold price monitoring, and ongoing financing oversight. The implementation of ISO 31000:2018-based risk management helps the bank manage risk systematically and structuredly, resulting in safer and more stable financing. This research is expected to contribute to the development of Islamic banking risk management, especially in gold installment financing products.